2018
DOI: 10.1371/journal.pone.0196913
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing exosomal RNA isolation for RNA-Seq analyses of archival sera specimens

Abstract: Exosomes are endosome-derived membrane vesicles that contain proteins, lipids, and nucleic acids. The exosomal transcriptome mediates intercellular communication, and represents an understudied reservoir of novel biomarkers for human diseases. Next-generation sequencing enables complex quantitative characterization of exosomal RNAs from diverse sources. However, detailed protocols describing exosome purification for preparation of exosomal RNA-sequence (RNA-Seq) libraries are lacking. Here we compared methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…Regarding the RNA isolation kit, we observed that miRNeasy kit showed higer number of miRNAs. Similar results were found by Prendergast et al 16 in serum samples. Phenol-based methods such as miRNeasy kit usually performed well but seemed to produce some bias 17 , as structured smRNAs with low GC content are recovered inefficiently when using low RNA quantities.…”
Section: Discusionsupporting
confidence: 91%
“…Regarding the RNA isolation kit, we observed that miRNeasy kit showed higer number of miRNAs. Similar results were found by Prendergast et al 16 in serum samples. Phenol-based methods such as miRNeasy kit usually performed well but seemed to produce some bias 17 , as structured smRNAs with low GC content are recovered inefficiently when using low RNA quantities.…”
Section: Discusionsupporting
confidence: 91%
“…This agrees with studies suggesting that EVs prepared by ultracentrifugation or precipitation polymers are comparable. 37,38 In samples prepared by ExoQuick ® , however, we found that the proportion of CD9 + CFSE + events was reduced when compared to non-purified samples and other isolation methods. This suggests that, despite providing a high yield of EVs, ExoQuick ® may insert EVs population bias.…”
Section: Comparison Of Purification Methods Of Evs By Fcmentioning
confidence: 76%
“…[1] Gene expression microarrays, qPCR and RNA sequencing can be used for the analysis of exosomal RNAs. [22] The progress of exosome isolation techniques has improved the efficiency of exosome isolation. However, the advantages and disadvantages of each technique needed to be taken into consideration when make choices.…”
Section: Exosomes Isolation Techniquesmentioning
confidence: 99%
“…For the downstream study, Western blot, fluorescence‐activated cell sorting (FACS), ELISA, trypsin digestion and mass spectrometry can be used for the analysis of exosomal proteins . Gene expression microarrays, qPCR and RNA sequencing can be used for the analysis of exosomal RNAs …”
Section: Introductionmentioning
confidence: 99%